1D Fibers and 2D Patterns Made of Quantum Dot‐Embedded DNA via Electrospinning and Electrohydrodynamic Jet Printing. Issue 2 (8th November 2018) - Arasu, Velu; Hwang, Sangyeon; Zhang, Bin; Byun, Doyoung; Park, Sung Ha
Abstract: Although DNA‐based 2D thin films are easily constructed, 1D fibers and 2D patterns made of DNA are seldom produced due to fabrication complexity. Here, the feasibility of constructing 1D fibers with various diameters and 2D patterns of any shape made of cetyltrimethylammonium chloride (CTMA)‐modified DNA (CDNA, which serves as an ink) via electrospinning and electrohydrodynamic (EHD) jet printing, respectively is demonstrated. The tunable parameters in electrospinning and EHD jet printing systems (e.g., applied bias voltage ( V ), printing speed ( S ), and flowrate ( F )) are evaluated and the photoluminescence characteristics, UV luminescence photographs, and confocal laser scanning microscope images of the 1D and 2D structures are analyzed. Based on the observations, the fiber diameter decreases as V increases for electrospinning. For EHD, the 1D line widths are inversely proportional to S and V and directly proportional to F . 2D free‐standing mats are also constructed by peeling the mats from the collector after completion of electrospinning. Finally, the QD‐embedded letters of "SKKU" are written on given substrates by an EHD system for verification of pattern drawing. The research gives perspective to construction of CDNA‐based functional scaffolds for bioengineering, stretchable fiber mats for flexible electronics, and direct printing of patterns for microchannel applications. Abstract : Although DNA‐based 2D thin films are easily constructed, 1D fibers and 2D patterns made of DNA are seldom produced due to their fabrication complexity. A DNA solution which serves as an ink in the electrospinning and electrohydrodynamic jet printing systems is developed. Then, the fibers, lines, mats, and letters with and without quantum dots are fabricated and characterized.